RACE CARS - James, Ryan; Walsh, Kathy; Thompson, Kim (Coral Springs, FL : Seahorse Publishing, 2023)
Join the car mania! It's time to shift gears and zoom onto the racetrack. Learn about the first car races, what special parts race cars have, and what kids of cars you'll find at formula races and NASCAR races.
Includes index
"A Stingray Book."
After Reading Questions. Includes a support page of teaching tips for caregivers and teachers. Downloadable Teacher's Notes available.
Keywords: Automobile racing -- Juvenile literature; Automobiles, Racing -- Juvenile literature; Automobiles, Racing -- History -- Juvenile literature; Muscle cars -- History -- Juvenile literature; Illustrated works; Informational works; History